The Role of Price and Product Quality in Increasing Consumer Purchase Interest (Marketing Management Literature Review) - Silviah, Reni (Greenation Research & Yayasan Global Resarch National, 2023)
Literature Review The Role of Price and Product Quality in Increasing Purchase Interest is a scientific article with the aim of analyzing whether price and product quality play a role in purchase interest. The method of writing a literature review article is the library research method, which is sourced from online media such as Google Scholar, and other online media. The results of this article are: 1) Price plays a role in Purchase Interest; 2) Product Quality plays a role in Purchase Interest. Apart from these 2 exogenous variables that influence the endogenous variable of Purchase Decisions, there are many other factors including customer satisfaction, consumer reviews, trust, brand image.